Micromethod for Assaying Serum Levels of Erythromycin - Bell, Stanley C. (1969)
A micromethod for assaying serum levels of erythromycin is described. The assay had the following characteristics: detection of 0.03 to 0.035 μg/ml, a long-range curve which minimizes sample dilution, 0.04 ml for a single measurement (0.3 ml required for full coverage), and utility for a variety of body fluids. The method employs radial diffusion from small paper discs which were saturated by capillary action rather than by dipping or pipetting. Although the method was designed to handle serum in which the sample volume is limited, statistical analysis demonstrated that the method has satisfactory precision for routine use. A study of 10 consecutive assays indicates a precision of ±12% at the 95% confidence limits. The method of least squares was used to calculate the line of best fit, and the statistics were developed on this basis. The assay method is applicable to a variety of antibiotics.